Perilaku Pembelian Produk Pakaian Bermerek Yang Dilakukan Staf Pengajar STIE Kesatuan Bogor - Puspitasari, Ratih; Mubarak, Mumuh Mulyana (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
Lifestyle and brand are the same with upper-middle class. There is parallelism between the famous brandand the personality. STIE Kesatuan lecturers can be the example in discussing lifestyle and brand.The purposes of this study are to find out the stage of brand preverance on clothes product, to alalyze the dominant factors that influence purchasing behaviour, and to analyze the behaviour after purchasing. This study is limited on purchasing behaviour by the lecturers and the factors which influence, the trend to choose upper-middle class brand products, and the action or behaviour after purchasing. The authors make a ranking on respondents based on data they collected, afterwards conclude brand preference stage.The ranking is arranged by percentage. The analysis is done by Image Analysis Method. The results of this study are (1) the brand preference of STIE Kesatuan lecturers is still in middle stage, (2) the dominant factor influencing customersâ purchase is product quality, (3) the dominant post-puchasing action is always choosing the upper-middle class brand products that give satisfaction, (4) the majority of respondents stated âitâs up toâ when their friends or their families are going to buy clothes.